The Personality and Divinity of the Holy Spirit - Agustin, Jr., Alfredo G. (8ISC Proceedings: Theology, 2022)
There are many issues surrounding the doctrine of the Trinity throughout the history of Christianity. Obviously, many church fathers espoused the doctrine of the Trinity. After along struggles with the Arians and other heresies, the Council of Nicea (A.D. 325) officially declared the doctrine of the Trinity. The locus of the controversy in the early years of Christianity was mainly on the divinity of Jesus. When this was finally settled, the controversy shifted on the Holy Spirit. But later on, this was also settled at the Council of Constantinople (A.D. 381). However, in the succeeding centuries, the issue of the Holy Spirit continued, which resulted in the schism between the Western and Eastern Christian Churches. The issue was mainly on the “procession” of the Holy Spirit. But the issue that is prevailing today, which already occurred in ancient times, is about the personality of the Holy Spirit. Some Christian scholars and churches deny the personality and divinity of the Holy, which is adhered to by the majority of Christian churches. It is now obvious that until today, the issue of the person and divinity of the Holy Spirit is still far from settled. Many books and articles have already been published on this issue. The task of this research is to re-investigate the evidence in the Scriptures, especially in the Gospels and Acts. This investigation will employ the historical-grammatical method of exegesis. This research is not an exhaustive exegetical exercise since it will deal with a large scope of materials. The procedure will follow the order found in the New Testament Bible, setting the issue on Synoptic Problem. This study adds more understanding about the exegetical analysis of the passages in the Gospels and Acts that deal with the Holy Spirit, which the author thinks are lacking. Keywords: Trinity, Holy Spirit, Divinity of the Holy Spirit, Personality of the Holy Spirit